2012
DOI: 10.3198/jpr2011.09.0517crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of Eight Six‐Rowed Feed Barley Germplasm Lines Resistant to Both Russian Wheat Aphid and Greenbug

Abstract: STARS 1006B (Reg. No. GP‐200, PI 659760), STARS 1007B (Reg. No. GP‐201, PI 659761), STARS 1008B (Reg. No. GP‐202, PI 659762), STARS 1009B (Reg. No. GP‐203, PI 659763), STARS 1010B (Reg. No. GP‐204, PI 659764), STARS 1011B (Reg. No. GP‐205, PI 659765), STARS 1012B (Reg. No. GP‐206, PI 659766), and STARS 1013B (Reg. No. GP‐207, PI 659767), are winter, six‐rowed, feed barley (Hordeum vulgare L.) germplasm lines developed cooperatively by the USDA‐ARS, in Stillwater, OK, and Aberdeen, ID as sources of resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Aphid and virus damage may be reduced by pesticide application, but access to efficient treatments against aphids begins to be limited due to product withdrawals and aphids becoming resistant to the control agents (Dewar and Foster 2017 ). Host resistance to aphids is an attractive alternative or complement to other control measures, and there are barley cultivars bred for resistance to Russian wheat aphid (RWA; Diuraphis noxia) and greenbug (GB; Schizaphis graminum) , even with combined resistance to both (Mornhinweg et al 2012 , 2017 ). As far as known there are no examples of breeding for resistance to R. padi leading to commercial varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Aphid and virus damage may be reduced by pesticide application, but access to efficient treatments against aphids begins to be limited due to product withdrawals and aphids becoming resistant to the control agents (Dewar and Foster 2017 ). Host resistance to aphids is an attractive alternative or complement to other control measures, and there are barley cultivars bred for resistance to Russian wheat aphid (RWA; Diuraphis noxia) and greenbug (GB; Schizaphis graminum) , even with combined resistance to both (Mornhinweg et al 2012 , 2017 ). As far as known there are no examples of breeding for resistance to R. padi leading to commercial varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, highly effective genetic resistance is available (Bregitzer et al, 2003), and agronomically unadapted R and MR accessions have been identified in the USDA-ARS National Small Grains Collection (http://ars.usda.gov/Main/docs.htm?docid = 21891). Selections from some of these accessions have been used to develop adapted resistant germplasm and cultivars (Bregitzer et al, 2003(Bregitzer et al, , 2005Mornhinweg et al, 1995Mornhinweg et al, , 1999Mornhinweg et al, , 2007aMornhinweg et al, , 2007bMornhinweg et al, , 2008Mornhinweg et al, , 2009Mornhinweg et al, , 2012aMornhinweg et al, , 2012b. Identification and development of these resources depended on phenotypic screens for resistance, which, although relatively simple and highly effective, provided little information on the genetic diversity for resistance.…”
Section: Researchmentioning
confidence: 99%
“…However, relatively few cultivars have been bred for resistance to their aphid pests so far. Among the examples are wheat and barley cultivars with resistance to one or both of Schizaphis graminis Rondani and Diuraphis noxia Kurdjumov ( Mornhinweg et al., 2012 ; Tolmay et al., 2015 ; Mornhinweg et al., 2017 ), soybean cultivars resistant to Aphis glycines Matsumura ( ; accessed on 11 November 2019), a lettuce cultivar resistant to Nasonovia ribisnigri (Mosley), and other aphid species ( ; accessed on 11 November 2019) and melon cultivars resistant to Aphis gossypii Glover ( Boissot et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%